2000
DOI: 10.1067/mtc.2000.108162
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and post-traumatic stress disorder in patients after cardiac surgery and intensive care treatment

Abstract: Patients who have had cardiac surgery demonstrate a high life satisfaction with an acceptable degree of physical and mental health-related quality of life. Impairments in psychosocial function and life satisfaction were found in a subgroup of patients with evidence of post-traumatic stress disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(97 citation statements)
references
References 25 publications
4
87
0
6
Order By: Relevance
“…[30]. Pitsburgo universiteto (Jungtinės Amerikos valstijos -JAV) ligoninės tyrėjai paskelbė nemažai duomenų apie PTSS po širdies transplantacijos [31,32].…”
Section: Psichikos Sveikatos Būklė Po Organo Transplantacijos Atliktunclassified
“…[30]. Pitsburgo universiteto (Jungtinės Amerikos valstijos -JAV) ligoninės tyrėjai paskelbė nemažai duomenų apie PTSS po širdies transplantacijos [31,32].…”
Section: Psichikos Sveikatos Būklė Po Organo Transplantacijos Atliktunclassified
“…Dies ist nicht üblich, da die Arbeiten weder leicht zugänglich sind, noch einem Peer-review-Verfahren unterzogen waren. Außerdem hat sie eine Arbeit von Stoll et al (2000) aufgenommen, die nicht Infarktpatienten, sondern kardiochirurgische PatientInnen einschließt. Diese 3 genannten Arbeiten werden in der vorliegenden Arbeit unberücksichtigt bleiben.…”
Section: Ergebnisseunclassified
“…In primis, the study of Stoll et al [111] compared patients undergoing cardiac surgery with healthy persons and those undergoing other types of surgery and noted a higher incidence of PTSD in cardiac surgery patients. The authors observed that patients after CABG with comorbid PTSD had a lower compliance with respect to use of medication, which carries the risk of an unfavorable course of the somatic disease.…”
Section: • Anxiety and Depressionmentioning
confidence: 99%